2013
DOI: 10.1096/fj.13-243840
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D3 receptor inhibits the ubiquitin‐specific peptidase 48 to promote NHE3 degradation

Abstract: The dopamine D3 receptor (D3R) is crucial in the regulation of blood pressure and sodium balance, in that Drd3 gene ablation in mice results in hypertension and failure to excrete a dietary salt load. The mechanism responsible for the renal sodium retention in these mice is largely unknown. We now offer and describe a novel mechanism by which D3R decreases sodium transport in the long term by inhibiting the deubiquitinylating activity of ubiquitin-specific peptidase 48 (USP48), thereby promoting Na(+)-H(+) exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 60 publications
1
24
0
Order By: Relevance
“…cells (Zeng et al, 2008;Yu et al, 2009). Recent evidence suggests dopamine D 3 receptor activation in the kidneys ultimately stimulates secretion of a sodium load (to reduce hypertension) by promoting degradation of the Na 1 -H 1 exchanger in renal proximal tubules (Armando et al, 2014). The pressor effect of the dopamine D 3 receptor antagonist in this study and its augmentation of cocaine's pressor effects are consistent with this body of evidence.…”
Section: Discussionsupporting
confidence: 86%
“…cells (Zeng et al, 2008;Yu et al, 2009). Recent evidence suggests dopamine D 3 receptor activation in the kidneys ultimately stimulates secretion of a sodium load (to reduce hypertension) by promoting degradation of the Na 1 -H 1 exchanger in renal proximal tubules (Armando et al, 2014). The pressor effect of the dopamine D 3 receptor antagonist in this study and its augmentation of cocaine's pressor effects are consistent with this body of evidence.…”
Section: Discussionsupporting
confidence: 86%
“…However, the physiologic function of USP48 remains largely unknown. One recent study demonstrates that USP48 deubiquitinates the Na + -H + exchanger (NHE3) and plays a role in blood pressure regulation (47). Tzimas et al (31) have shown that USP48 is involved in the inhibition of NF-kB activation, a theme also presented in the study by Schweitzer and Naumann (32) in which the COP9 signalosome (CSN) and USP48 cooperatively control the nuclear turnover of RelA.…”
Section: Discussionmentioning
confidence: 91%
“…However, "cycloheximide chase" has an intrinsic limitation on determining degradation of long-lived proteins due to the potential effects of prolonged protein synthesis inhibition on overall cell function (40), and hence, we cannot completely rule out the role of ubiquitination in hNHE3 degradation based on the current results. While this work was being pursued, Armando et al (41) reported that dopamine inhibited NHE3 in hRPTC human renal proximal tubule cells by inhibition of the deubiquitinating activity of Ub-specific ligase 48, USP48. Inhibition of USB48, which removes Ub from NHE3, decreased the half-life of NHE3 and enhanced NHE3 degradation.…”
Section: Discussionmentioning
confidence: 99%